Effect of sodium hydroxide pretreatment on released sugar yields from pomelo peels for biofuel production - Chatkaew Chaichana; Panakkal Elizabeth Jayex; Rodiahwati Wawat; Kirdponpattara Suchata; Chuetor Santi; Sriariyanun Malinee; Cheenkachorn Kraipat (E3S Web of Conferences, 2021)
Most of the agricultural wastes in developing countries are disposed of by on-site combustion leading to unmanaged environmental pollutions. Conversion of agricultural wastes to value-added products, such as bioethanol and biogas, is a promising method to reduce agro-waste after harvesting seasons. In this study, Citrus maxima peels (Pomelo peels) was selected to be converted to reducing sugars, which could be a raw material to produce other value-added products. To promote enzymatic hydrolysis reactions, pomelo peels were pretreated with sodium hydroxide by variations of three pretreatment parameters, including temperature (50-100 ºC), time (0.5-6 h), and concentration of NaOH (0.5-3.0 M). Box-Behnken design (BBD) was applied in Response Surface Methodology (RSM) to determine the optimized pretreatment condition and to find the relationship between pretreatment factors and reducing sugar yields. The predicted optimal pretreatment condition was determined to be at 94.28 ºC, 4.5h, 2.17M with reducing sugar yield of 98.9 mg/g of dried pomelo peels. The results clearly showed that reducing sugar yields obtained from pretreated pomelo peels were 1.87 folds higher than untreated biomass (52.81 mg/g of pomelo peels). Therefore, this study demonstrated the potential of pomelo peels to be used as an alternative raw material for value-added products rather than being a landfill or causal agent of pollution.